2005
DOI: 10.1074/jbc.m411514200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mRNA Splicing of SMRT Creates Functional Diversity by Generating Corepressor Isoforms with Different Affinities for Different Nuclear Receptors

Abstract: Many eukaryotic transcription factors are bimodal in their regulatory properties and can both repress and activate expression of their target genes. These divergent transcriptional properties are conferred through recruitment of auxiliary proteins, denoted coactivators and corepressors. Repression plays a particularly critical role in the functions of the nuclear receptors, a large family of ligand-regulated transcription factors involved in metazoan development, differentiation, reproduction, and homeostasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 82 publications
3
74
0
Order By: Relevance
“…We determined if the HCC mutations altered the relative affinity of TRb1 for SMRT versus N-CoR. As shown in prior studies (Zamir et al, 1997;Goodson et al, 2005), wild-type TRb1 interacted more weakly with GST-SMRT than with GST-N-CoR in the absence of hormone, but released from both corepressors at comparable T3 concentrations (Figure 2b, solid line). Interestingly, the affinities of the TRb1 HCC mutants for SMRT versus N-CoR differed.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We determined if the HCC mutations altered the relative affinity of TRb1 for SMRT versus N-CoR. As shown in prior studies (Zamir et al, 1997;Goodson et al, 2005), wild-type TRb1 interacted more weakly with GST-SMRT than with GST-N-CoR in the absence of hormone, but released from both corepressors at comparable T3 concentrations (Figure 2b, solid line). Interestingly, the affinities of the TRb1 HCC mutants for SMRT versus N-CoR differed.…”
Section: Resultsmentioning
confidence: 79%
“…Wild-type and mutant TRs were also cloned into pFastBac1 (Invitrogen, Carlsbad, CA, USA) using EcoRI restriction sites for the TRb1 clones and EcoRI (5 0 ) and HindIII (3 0 ) for the TRa1 clones, and wild-type TRa1 and TRa1-I were cloned into pCI-neo using EcoRI (5 0 ) and NotI (3 0 ). The pSG5-wild-type TRb1, pSG5.2 expression vector, DR4-thymidine kinase promoter (TK)-luciferase reporter, AP-1 collagenase luciferase reporter, pRSV-c-jun, pGEX-MPa-SRC1, pGEX-MPc-SMRT and pGEX-N-CoR constructs were previously described (Weinberger et al, 1986;Sharif and Privalsky, 1992;Wong and Privalsky, 1998;Jonas and Privalsky, 2004;Goodson et al, 2005).…”
Section: Molecular Clonesmentioning
confidence: 99%
“…RBPJ is in repressive complexes containing NCoR1 and -2, SKIP, and SHARP (17)(18)(19)(20)(21)(22)(23). NCoR recruits class I and II histone deacetylases (HDAC), including HDAC3, which repress transcription and associate with matrix-associated deacetylase (MAD) bodies, subnuclear sites of repressed transcription (24,25).…”
mentioning
confidence: 99%
“…Whereas c-Erb A binds N-CoR more strongly than SMRT (Cohen et al, 1998(Cohen et al, , 2000(Cohen et al, , 2001Webb et al, 2000;Makowski et al, 2003;Goodson et al, 2005;Zamir et al, 1997), we found that v-Erb A displayed a nearequal interaction with SMRT as with N-CoR. Restoring the c-Erb A helix 12 to v-Erb A restored the c-Erb A preference for N-CoR.…”
Section: Discussionmentioning
confidence: 52%
“…As anticipated, both v-Erb A SMRT corepressor is closely related to N-CoR but differs in its affinity for different nuclear receptors (Privalsky, 2004). Although alternative mRNA splicing can produce corepressors with differing receptor affinities, c-Erb A generally interacts more strongly with NCoR than with SMRT (Zamir et al, 1997;Cohen et al, 1998Cohen et al, , 2000Cohen et al, , 2001Webb et al, 2000;Makowski et al, 2003;Goodson et al, 2005). To examine this question for v-Erb A, we tested SMRT constructs in place of NCoR in our EMSA supershifts.…”
Section: Substitutions In the V-erb A I-box Enhance Homodimerization mentioning
confidence: 99%